Studies on Period of Oviposition and Hatching of Eggs in Hyalomma anatolicum anatolicum - Prasad, L; Bagherwal, RK; Jayraw, AK; Rajput, N; Thankur, P (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The engorged Hyalomma anatolicum anatolicum females were collected from healthy cattle of college farm as well as nearby private dairy farms and villages of Mhow to evaluate the period of oviposition and hatching of eggs of H. a. anatolicum under laboratory conditions. The present study recorded the period of oviposition and hatching of eggs (Mean ± SE) as 9.4 ± 0.54 and 21.9 ± 0.69 days, respectively. acaricide application and using anti-tick vaccine. Hyalomma anatolicum anatolicum is a widely distributed multi-host tick infesting cattle, buffaloes, sheep and goats responsible for transmitting Theileria annulata, T. buffeli and T. lestocardi (T. hirci) in India (Ghosh and Azhahianambi, 2007). Depending on atmospheric conditions, variation is observed in period of oviposition and hatching of eggs. The period of oviposition and hatching of eggs varies upon Hence, owing to scanty literature pertaining to Hyalomma anatolicum anatolicum compared to Rhipicephalus (Boophilus) microplus. The present study was designed to know the normal of period oviposition and hatching of eggs in case of H. a. anatolicum